PENGARUH MOTIVASI KERJA, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA OPERATOR SEKOLAH DASAR NEGERI DI KABUPATEN KOTAWARINGIN TIMUR - Ruskadiyana, R; Mangkunegara, Anwar (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study was to establish and analysze the impact of variable motivation, competence and compensation on  operator’s performance Elementary School in East Kotawaringin both partially or simultaneously. This study is a quantitative research methods using the statistical parametric and regression analysis. There the data is processed using SPSS 21. In this study, all operators of public elementary school in East Kotawaringin of 310 people. The instruments used in the form of a structured questionnaire and measured using a Likert scale with intervals of 1-5, the instrument consists of 42 questions and statements that have been prepared based on the dimensions and indicators based on survey variable. The results showed that; motivation, competence and compensation positive and significant rated correlation or low level positive relationship with partial or simultan effect on the variable performance controller. It is expected in the future can be used as a source of data for future research related to the operator and to conduct further research based on other factors, the different variables and different places